Isotope investigations of groundwater from Ljubljansko polje (Slovenia) - Urbanc, Janko; Jamnik, Brigita (Geologija, 1998)
Two components of different origin occur in the groundwater of the sand-gravelly aquifer Ljubljansko polje: locally infiltrated precipitation and water from the Sava river. The proportion of both components was assessed on the basis of groundwater oxygen isotope composition. During the observation period, the Sava river component was represented by 19 to 100 % of the total groundwater volume in individual wells.